BUCCAL CORRIDOR YANG LEBIH MENARIK PADA ESTETIK SENYUM - Nety Trisnawaty (Odonto : Dental Journal, 2017)
Background: The objectives of orthodontic treatment are not only to obtain functional occlusion but also to improve facial and dental aesthetics. Three aspects of smile aesthetics have recently received great attention: the amount of gingival display, the presence of the smile arc, and buccal corridor spaces.The purpose of this study was to evaluation that the amount of buccal corridor on smile esthetics of dentists and dental students.Method: The population and subjects this study were dentists and dentalstudents of dental school from Faculty of Dentistry University Prof. Dr. Moestopo (Beragama). Using a Visual Analog Scale (VAS), dentists and  dental students rated the attractiveness of six smiles with altered buccal corridors.Result: There was no significant different in judging the effect of buccal  corridors on the smile attractiveness between dentists and dental students.Conclusion: Both the dentists and dental students preferred medium sizes of buccal corridor (buccal corridor 15%).